(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Ethnography is one of the oldest methods in qualitative research rooted in anthropology. Considering that Indonesia is rich in the diversity of vernacular architecture and the culture of its people, ethnography, which means ’the study of culture’, is often an option for architectural research. However, architectural research frequently only adopts the steps of the anthropological ethnographic method to reveal the cultural knowledge of a specific community; then, this cultural knowledge is simply applied to justify specific architectural works. This study aims to formulate a new architectural-ethnographic method. Of all types of ethnography, this study elaborates on ethnosemantics put forward by James Spradley. The rigorous analytical steps of ethnosemantic are then elaborated into a theory of architectural ordering principle based on the existential needs of architecture. The results of the study are expected to enrich architectural science, especially in terms of research methods. Thus, the results of this study can also improve existing architectural theories and practices, as well as become a source of new knowledge for the wider community.